Psychological Distress in Married Females Under 18 in Pashtun Culture of Pakistan: A Quantitative Study (Journal of Social Sciences Review, 2025)
Early marriage is prevalent in many parts of Pakistani society, particularly within Pashtun culture, where it is often encouraged due to conservative mindsets. This cultural norm promotes marriage before the age of 18, which can lead to psychological distress in women, such as depression, anxiety, and stress. However, despite the significance of this issue in Pashtun culture, relevant studies remain scarce. Therefore, the current study aims to explore the relationship between depression, anxiety, and stress among females under the age of 18 in the Pashtun culture of Pakistan. The study adopted a correlational research design and used a snowball sampling technique to collect data from 356 females aged 13 to 17, with the consent of their guardians. Data were collected using the Depression, Anxiety, and Stress Scale (DASS) to assess levels of psychological distress. Correlational analysis revealed a significant and positive relationship among depression, anxiety, and stress. Furthermore, anxiety and stress were found to significantly predict depression in these females. An independent samples t-test showed that rural married females scored significantly higher on stress and anxiety compared to their urban counterparts. Although urban females scored lower on depression than rural females, the difference was not statistically significant. The study's comprehensive implications include raising mental health awareness to help prevent early marriages, with the involvement of mental health professionals, media, and journalists. Additionally, the government should take strict action to prevent early marriages and ensure that women are granted the human rights they deserve.
Keywords: Pashtun Culture; Married; Female